DETERMINASI PENENTUAN HARGA JUAL DENGAN ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING - Safrizal Safrizal (Accounting Journal of Ibrahimy (AJI), 2024)
High competition in this business means that doll industry players must start improving the quality and creativity of the products they produce, so that they can attract market share. AZR Collection Convection is a business that operates in the field of making dolls of various characters. The aim of the research is to compare the calculation of the costs of production carried out by the company and the full costing method so that the right selling price can be found to produce maximum profit for doll production. Quantitative descriptive is the research method used. The results of this research show that the cost of production using the full costing method results in higher production costs compared to the company method used by the company. These findings reveal that the methods used by the company do not fully accommodate all costs incurred, so there are differences in the profits generated.